UI/UX Design of the Bangkitku Waste Bank Information System in Jambi City Using Design Thinking - Sopia Ranty; Reni Aryani; Zainil Abidin; Noneng Marthiawati; Winny Laura (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2025)
Waste management is increasingly critical due to the rising waste generated by community activities driven by a consumptive lifestyle. A key solution to this issue is the implementation of waste bank programs, though community participation and operational efficiency remain challenges, as seen with the Bangkitku Waste Bank in Jambi City. This study focuses on designing the user interface for the Bangkitku Waste Bank Information System using the design thinking method and evaluating the usability of the prototype. The design process followed the five stages of design thinking: empathize, define, ideate, prototype, and test, with data collected through interviews and observations. The analysis involved tools such as empathy maps, user personas, sitemaps, and user flows, with prototypes created using Figma. Usability testing was conducted with 10 participants, including administrators and customers, resulting in high usability scores—98 for administrators and 97 for customers. The majority of participants found the system easy to use, as indicated by responses on the Single Ease Question (SEQ) survey. The prototype met key usability criteria, improving both operational efficiency and community engagement in waste bank management. The findings demonstrate the system's potential to foster sustainable environmental practices and enhance the effectiveness of waste bank management.